Between two trees: Environmental effects of I. micheliana and A. latifolia on leaf litter ants in a coffee agroecosystem. Issue 2 (21st February 2023) - Aponte Rolón, Bolívar; Perfecto, Ivette
Abstract: Shade trees provide important ecological services that support productivity in coffee agroforestry systems. Processes such as biological nitrogen fixation play a key role in this. Less is known, however, about potential indirect mechanisms by which nitrogen fixation supports coffee productivity. One potential route for this to occur is by providing ecological benefits to other above‐ and belowground organisms that enrich the overall function of agroecosystems. A useful lens with which to evaluate the ecological benefits to these communities under shade trees is to assess how ground‐dwelling ant communities respond to the quality of leaf litter from established nitrogen (N)‐fixing tree species. Here, we use two trees commonly planted in coffee agroecosystems: Inga micheliana, an N‐fixing species, and Alchornea latifolia, a non‐N‐fixing species. In this study, we set out to answer the following questions: (1) How does the leaf litter environment differ between I. micheliana and A. latifolia ? (2) Do differences in environmental factors between I. micheliana and A. latifolia correlate with differences in ant abundance and species richness? and (3) Do differences in environmental factors between I. micheliana and A. latifolia correlate with differences in ant community composition? Twenty‐eight randomly selected sites (14 I. micheliana and 14 A. latifolia ) were established within a 45‐ha plot in a shaded organic coffee farm in Chiapas, Mexico. Three 1‐m 2 quadrats within a 5‐m radius from the base of the selected trees were established, and the leaf litter within the quadrats was removed and sieved. Ant specimens were extracted from leaf litter collected from quadrats using the mini‐Winkler method and identified to genus and species, or morphospecies, level. Results indicate that I. micheliana, the N‐fixing species, has a lower C:N ratio than A. latifolia . Differences in C:N ratios are correlated with ant abundance but not with ant species richness. Distance to edge (in meters) has significant effects on leaf litter ant abundance, richness, and species composition. Results suggest that there may be unaccounted feedbacks from N‐ and non‐N‐fixing vegetation to brown food webs enabling them to sustain similar ground‐dwelling ant communities.